TEKRARLAYAN KARIN AĞRISI NEDENİYLE ENDOSKOPİ YAPILAN ÇOCUK OLGULARIN DEĞERLENDİRİLMESİ - KAYAOKAY, ABDULLAH MURAT (Fırat Üniveristesi, 2016)
Çocukluk çağı tekrarlayan karın ağrısının tanı ve tedavisinde son yıllarda gastrointestinal sistem endoskopisi daha sık kullanılmaya başlanmıştır. Endoskopinin tekrarlayan karın ağrısının tanı ve tedavisinde kullanımına yönelik olarak birçok klinik çalışma mevcuttur. Bu çalışmalarda birbirinden farklı sonuçlar elde edilmiştir. Bu klinik çalışmanın amacı bölgemizde çocukluk çağı tekrarlayan karın ağrısı nedeniyle endoskopi yapılmış olguların klinik ve laboratuvar özelliklerini incelemeyi planlanmıştır. Karın ağrısı ile gelip endoskopi yapılan toplam 541 hasta vardı. Bu hastaların 201(%37.2)'i erkek, 340(%62.8)'ı kız idi. Tekrarlayan karın ağrısı olan 541 olguda karın ağrısı dışında en sık eşlik eden yakınma %3.5'inde (19 olgu) kusma, ishal %0.9'unda (5 olgu), kanlı dışkılama %0.3'ünde (2 olgu), kanlı kusma %0.1 (1 olgu), sarılık %0.1'inde (1 olgu) ve kabızlık %0.1'inde (1 olgu) saptandı. Tekrarlayan karın ağrısı olan 541 hastanın yapılan endoskopilerinde makroskopik bulgulardan sırasıyla en sık midede hiperemi %76.1'inde (412 olgu), midede nodülarite %23.1'nde (125 olgu), duodenumda düzensizlik %9.7'sinde (53 olgu), midede ülser %2.2'sinde (12 olgu), duodenumda ülser % 1.4 'ünde (8 olgu), özefagusta polip % 0.2'sinde (1 olgu) izlendi. Endoskopi yapılan 541 hastanın 500'ünde histopatolojik tanı açısından biyopsi gönderilmişti. Olguların %52,6'sında ( 263 olgu) Helikobacter Pylori pozitifliği saptandı. Erkek hastaların %49,2'inde (11 olgu), kız hastaların ise %54.8'sinde ( 171 olgu) HP pozitifliği saptandı. Erkek ve kız cinsiyet arasında HP açısından istatistiksel olarak anlamlı bir farklılık saptanmadı.(p=0.2) . Son yıllarda tekrarlayan karın ağrısının organik nedenlerinde artış gözlemlenmektedir. Organik nedenli karın ağrısının erken tanı ve tedavisi ile komplikasyonlar önlenebilmektedir. Anahtar Kelimeler: Tekrarlayan karın ağrısı, endoskopi, çocuk

Recently; gastrointestinal system endoscopy have begun to be used in diagnosis and therapy of childhood recurrent abdominal pain. In our country; there is many clinical study devoted to endoscopy's usage in diagnosis and therapy of recurrent abdominal pain. In studies that have been done so far several results have been obtained. Within the frame of this clinical study; we planned to analyze the clinical and laboratorial features of the facts that are subjected to endoscopy because of childhood recurrent abdominal pain in Eastern Anatolia Region. There were 541 patients that applied with abdominal pain and then subjected to endoscopy. 201 (37.2%) of these patiens were boys, and 340 (62.8%) of them were girls. In 541 facts that have recurrent abdominal pain; we have determined that in 3.5% (19 facts) of the most frequent comorbidit complaints were vomitting, 0.9% (5 facts) of them were diarrhea, 0.3% (2 facts) were bloody stool, 0.1& (1 fact) of them was vomiting blood, 0.1% (1 fact) was hepatitis and 0.15 (1 fact) was constipation. In endoscopies of the 541 patients that have recurrent abdominal pain; we have monitored in order most frequently hyperaemia in the stomach in 76.1% (412 facts) of the patiens, nodularity in the stomach in 23.1% (125 facts), irregularity in duodenum in 9.7% (53 facts), ulcer in the stomach in 2.2% ( 12 facts), ulcer in duodenum in 1.4% (8 facts) and polyp in oesophagus in 0.2% (1 fact) of macroscopic symptoms. In the aspect of histopathologic diagnosis; a biopsy was sent to 500 of the 541 patients subjected to endoscopy. In 52.6% (263 facts) of the facts HP positiveness was detected. In 49.2% (11 facts) of the boys and in 54.8% (171 facts) of the girls HP positiveness was tedected. A statistically significant difference was not detected between boy and girl genders. (P= 0.2) Aspartate aminotransferase values analyzed between the patiens that have normal endoscopies and the patiens that has pathologies detected to be high in a statistically significant way (P<0.05). An increase have been observed in the organic causes of recurrent abdominal pain in recent years. Complications can be prevented with early diagnosis and threapy of organically cauesed recurrent abdominal pain. Key Words: Recurent abdominal pain, children, endoscopy
Evaluation of children's case due to the endoscopy recurrent abdominal pain
Keywords: Çocuk Sağlığı ve Hastalıkları